2022
DOI: 10.1155/2022/1195875
|View full text |Cite|
|
Sign up to set email alerts
|

Research Progress of PI3K/PTEN/AKT Signaling Pathway Associated with Renal Cell Carcinoma

Abstract: Renal cell carcinoma is a common renal malignancy of the urinary system and the most malignant type of kidney cancer. Phosphatidylinositol 3-kinase (PI3K) is an intracellular phosphatidylinositol kinase associated with oncogene products such as v-src and with serine/threonine kinase activity, and its increased activity correlates with the development of several cancers. Protein kinase B (AKT) is a cyclic guanosine phosphate-dependent protein kinase that plays an important role in cell survival and apoptosis. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…PTEN (phosphatase and tensin homolog), which was recently identified as a tumor suppressor gene with bispecific phosphatase activity, is also a gene that is second only to the P53 gene in its close relationship to carcinogenesis and plays an important role in cell proliferation, apoptosis, adhesion, migration, and infiltration (Liu et al, 2022;Fang et al, 2022). PTEN is frequently inactivated in various malignancies, such as brain, prostate, endometrial, gastric cancers and NSCLC, and clinical data have suggested that PTEN loss of function occurs in 10%-25% of NSCLC cases (Liu et al, 2022).…”
Section: Ptenmentioning
confidence: 99%
See 1 more Smart Citation
“…PTEN (phosphatase and tensin homolog), which was recently identified as a tumor suppressor gene with bispecific phosphatase activity, is also a gene that is second only to the P53 gene in its close relationship to carcinogenesis and plays an important role in cell proliferation, apoptosis, adhesion, migration, and infiltration (Liu et al, 2022;Fang et al, 2022). PTEN is frequently inactivated in various malignancies, such as brain, prostate, endometrial, gastric cancers and NSCLC, and clinical data have suggested that PTEN loss of function occurs in 10%-25% of NSCLC cases (Liu et al, 2022).…”
Section: Ptenmentioning
confidence: 99%
“…Furthermore, evidence suggests that the activation of PI3K/AKT signaling pathway contributes to cancer therapeutic resistance, including resistance to conventional chemotherapy, immunotherapy and agents targeting other oncogenic drivers. Drug resistance may be efficiently reduced by inhibiting PI3K/ AKT signaling (Fang et al, 2022). PTEN can also affect tumor proliferation and migration through other pathways.…”
Section: Ptenmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%